Pulse wave velocity is associated with increased plasma oxLDL in ageing but not with FGF21 and habitual exercise - Lee, Shuen Yee (2021)
Fibroblast growth factor 21 (FGF21) and adiponectin increase the expression of genes involved in antioxidant pathways, but their roles in mediating oxidative stress and arterial stiffness with ageing and habitual exercise remain unknown. We explored the role of the FGF21-adiponectin axis in mediating oxidative stress and arterial stiffness with ageing and habitual exercise. Eighty age- and sex-matched healthy individuals were assigned to younger sedentary or active (18-36 years old, n = 20 each) and older sedentary or active (45-80 years old, n = 20 each) groups. Arterial stiffness was measured indirectly using pulse wave velocity (PWV). Fasted plasma concentrations of FGF21, adiponectin and oxidized low-density lipoprotein (oxLDL) were measured. PWV was 0.2-fold higher and oxLDL concentration was 25.6% higher (both p < 0.001) in older than younger adults, despite no difference in FGF21 concentration (p = 0.097) between age groups. PWV (p = 0.09) and oxLDL concentration (p = 0.275) did not differ between activity groups but FGF21 concentration was 9% lower in active than sedentary individuals (p = 0.011). Adiponectin concentration did not differ by age (p = 0.642) or exercise habits (p = 0.821). In conclusion, age, but not habitual exercise, was associated with higher oxidative stress and arterial stiffness. FGF21 and adiponectin did not differ between younger and older adults, meaning that it is unlikely that they mediate oxidative stress and arterial stiffness in healthy adults.